Distinguishing in‐hospital and out‐of‐hospital status epilepticus: clinical implications from a 10‐year cohort study. (20th July 2017) - Sutter, R.; Semmlack, S.; Spiegel, R.; Tisljar, K.; Rüegg, S.; Marsch, S.
Abstract : Background and purpose: The aim was to determine differences of clinical, treatment and outcome characteristics between patients with in‐hospital and out‐of‐hospital status epilepticus (SE). Methods: From 2005 to 2014, clinical data were assessed in adults with SE treated in an academic medical care centre. Clinical characteristics, treatment and outcomes were compared between patients with in‐hospital and out‐of‐hospital SE. Results: Amongst 352 patients, 213 were admitted with SE and 139 developed in‐hospital SE. Patients with in‐hospital SE had more acute/fatal aetiologies (60% vs. 35%, P < 0.001), fewer previous seizures (33% vs. 50%, P = 0.002), a higher median Charlson Comorbidity Index (3 vs. 2, P < 0.001), longer median SE duration (1 vs. 0.5 days, P = 0.001), more refractory SE (52% vs. 39%, P = 0.022), less return to functional baseline (38% vs. 54%, P = 0.006) and increased mortality (29% vs. 19%, P = 0.001). Whilst in multivariable analyses an increasing Status Epilepticus Severity Score (STESS) was an independent predictor for death in both groups, increased Charlson Comorbidity Index and treatment refractory SE were associated with death only in patients with in‐hospital SE. Continuous anaesthesia for refractory SE was associated with increased mortality only in patients with out‐of‐hospital SE. The area under the receiver operating curve was 0.717 for prediction of death by STESS in patients with in‐hospital SE and 0.811 in patients with out‐of‐hospital SE. Conclusions: Patients with in‐hospital SE had more fatal aetiologies and comorbidities, refractory SE, less return to functional baseline, and increased mortality compared to patients with out‐of‐hospital SE. Whilst the STESS was a robust predictor for death in both groups, the association between continuous anaesthesia and death was limited to out‐of‐hospital SE.